2020
DOI: 10.3390/nu12051484
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aronia melanocarpa Juice Consumption on the mRNA Expression Profile in Peripheral Blood Mononuclear Cells in Subjects at Cardiovascular Risk

Abstract: Foods and food products that contain polyphenols are proposed to modulate risk of cardiovascular disease. The aim of this three-arm, crossover, randomized, double-blind, placebo-controlled intervention study was to examine the impact of Aronia melanocarpa juice (AMJ), high-polyphenol (AMJ treatment, 1.17 g/100 mL polyphenols) and low-polyphenol (dAMJ treatment, 0.29 g/100 mL polyphenols) dose, on the transcriptome in peripheral blood mononuclear cells (PBMC) of 19 subjects at cardiovascular risk. Transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…This has been supported by several pilot studies and a meta-analysis for Aronia berries, which showed that regular consumption of Aronia juice can reduce the incidence of urinary tract infection and the use of antibiotics of elderly residents of nursing homes [50] and decrease blood pressure and total cholesterol levels to show potential cardioprotective effects [60][61][62][63][64][65]. In addition, Aronia berries were found to show immunomodulating activity [55,56,59], and they exhibited synergistic effects with elderberries for their inhibitory potency against β-coronavirus-1 (HCoV-OC43) [53]. Thus, the fruits of A. melanocarpa could be used with other agents to enhance their pharmaceutical properties in future development efforts.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This has been supported by several pilot studies and a meta-analysis for Aronia berries, which showed that regular consumption of Aronia juice can reduce the incidence of urinary tract infection and the use of antibiotics of elderly residents of nursing homes [50] and decrease blood pressure and total cholesterol levels to show potential cardioprotective effects [60][61][62][63][64][65]. In addition, Aronia berries were found to show immunomodulating activity [55,56,59], and they exhibited synergistic effects with elderberries for their inhibitory potency against β-coronavirus-1 (HCoV-OC43) [53]. Thus, the fruits of A. melanocarpa could be used with other agents to enhance their pharmaceutical properties in future development efforts.…”
Section: Discussionmentioning
confidence: 80%
“…A three-arm, crossover, randomized, double-blind, and placebo-controlled intervention study was conducted to examine the impact of Aronia berry juice on the transcriptome in peripheral blood mononuclear cells from 19 subjects at cardiovascular risk. The results indicate that the prolonged habitual consumption of phenol-rich Aronia juice may lead to immunomodulatory activity mediated by different biological pathways [59]. A parallel and placebo-controlled study was performed to determine the impact of a four-week period of daily consumption of phenol-rich Aronia juice on long interspersed nucleotide element-1 (LINE-1) DNA methylation in peripheral blood leukocytes and on plasma polyunsaturated fatty acids (PUFA) profiles in subjects with a risk of cardiovascular disease.…”
Section: Potential Benefits To the Prevention And Treatment Of Cardio...mentioning
confidence: 93%
“…Similar results presented in Table 1 are also observed with the transition of anthocyanins. The total content of anthocyanins in osmotic solutions (195.13±0.25 mg/100 g) is higher than in chokeberry juice (150 mg/100 g) [24]. The traditional drying method reduces the anthocyanin content by 41 %.…”
Section: Discussion Of the Results Of The Study Of The Antioxidant Po...mentioning
confidence: 94%
“…It has been shown that anthocyanins in chokeberry extract, constituting 34 % of the total phenolic content, are intensively metabolized [23]. The total anthocyanin content in chokeberry juice ranged from 0.15 to 3.04 g/l [24]. When using traditional juice production technology with high pasteurization temperatures, the anthocyanin content is reduced by 93 % [25].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The following experiments were performed as previously described [ 34–37 ]. PBMCs were isolated using the lymphocyte isolate (Ficoll solution) from the peripheral blood of 200 tumor patients (the patient information is summarized in Table 1 ) to construct a scFv immune library.…”
Section: Methodsmentioning
confidence: 99%